Tailored axillary surgery in patients with clinically node-positive breast cancer: Pre-planned feasibility substudy of TAXIS (OPBC-03, SAKK 23/16, IBCSG 57-18, ABCSG-53, GBG 101). (December 2021) - Weber, Walter P.; Matrai, Zoltan; Hayoz, Stefanie; Tausch, Christoph; Henke, Guido; Zwahlen, Daniel R.; Gruber, Günther; Zimmermann, Frank; Seiler, Stefanie; Maddox, Charlotte; Ruhstaller, Thomas; Muenst, Simone; et al.
Abstract: Aim: We developed tailored axillary surgery (TAS) to reduce the axillary tumor volume in patients with clinically node-positive breast cancer to the point where radiotherapy can control it. The aim of this study was to quantify the extent of tumor load reduction achieved by TAS. Methods: International multicenter prospective study embedded in a randomized trial. TAS is a novel pragmatic concept for axillary surgery de-escalation that combines palpation-guided removal of suspicious nodes with the sentinel procedure and, optionally, imaging-guided localization. Pre-specified study endpoints quantified surgical extent and reduction of tumor load. Results: A total of 296 patients were included at 28 sites in four European countries, 125 (42.2%) of whom underwent neoadjuvant chemotherapy (NACT) and 71 (24.0%) achieved nodal pathologic complete response. Axillary metastases were detectable only by imaging in 145 (49.0%) patients. They were palpable in 151 (51.0%) patients, of whom 63 underwent NACT and 21 had residual palpable disease after NACT. TAS removed the biopsied and clipped node in 279 (94.3%) patients. In 225 patients with nodal disease at the time of surgery, TAS removed a median of five (IQR 3–7) nodes, two (IQR 1–4) of which were positive. Of these 225 patients, 100 underwent ALND after TAS, which removed a median of 14 (IQR 10–17) additional nodes and revealed additional positive nodes in 70/100 (70%) of patients. False-negative rate of TAS in patients who underwent subsequent ALND was 2.6%. Conclusions: TAS selectively reduced the tumor load in the axilla and remained much less radical than ALND. Highlights: Tailored axillary surgery is a novel concept for clinically node-positive breast cancer Tailored axillary surgery selectively removes positive lymph nodes Tailored axillary surgery is much less radical than axillary dissection Tailored axillary surgery removes the clipped node in the vast majority of patients